Explanatory risk factors in the relations between schizotypy and indicators of suicide risk. (30th April 2016) - Jahn, Danielle R.; DeVylder, Jordan E.; Hilimire, Matthew R.
Abstract: Schizotypy has been linked to suicide risk, but it is not known whether established suicide-related risk factors mediate this relation. The aim of this study was to assess the mediating effects of depressive symptoms, social anxiety, self-esteem, and intimate disclosure in peer relationships in the relation between interpersonal schizotypy and suicide ideation or lifetime suicide attempts. This aim was tested in 590 young adults using a nonparametric bootstrapping procedure. After inclusion of the mediators, interpersonal schizotypy was no longer directly associated with either suicide ideation or lifetime suicide attempts. Depression and self-esteem mediated the relation between interpersonal schizotypy and suicide ideation. No variables mediated the relation between interpersonal schizotypy and lifetime suicide attempts, and there were no significant direct relations when mediators were included. Schizotypy appears to be a distal risk factor for suicidal behavior; assessing depressive symptoms and self-esteem may provide more proximal information about suicide risk, and may be targets for mitigating suicide risk in individuals with schizotypy. Highlights: Depression and self-esteem mediate the relationship between interpersonal schizotypy and suicide ideation. Social anxiety and disclosure in relationships do not explain the relationship between schizotypy and suicide risk. Schizotypy is a distal suicide risk factor, and other well-established risk factors may provide more useful information.